Reliability and validity of two in vivo measurements for skin surface topography in aged adults - Trojahn, C.; Schario, M.; Dobos, G.; Blume-Peytavi, U.; Kottner, J. (Skin research and technology, 2015)
Background The non‐contact optical methods phaseshift rapid in vivo measurement of skin (PRIMOS) and surface evaluation of living skin (SELS) are widely applied for measuring skin surface topography. The aims of the present study were to evaluate reliability and validity of these methods and to compare skin roughness intraindividually. Methods SELS and PRIMOS measurements were performed on four skin areas of the left and right volar forearms in 12 healthy elderly subjects. Reliability and correlations were analyzed for Visioscan® and PRIMOS roughness parameters. Student's t‐tests for estimating differences between contralateral volar forearm sites were applied. Results ICC coefficients of the Visioscan® roughness estimates ranged between 0.50 and 0.95 and of the PRIMOS measurements between 0.01 and 1.00. The Visioscan® parameters SEr, SEsm, Rmax, and Rz, and the PRIMOS parameters Ra, Rz, Smax, Wt, and Sz showed most significant correlations with each other and to additional roughness parameters. Mean roughness differences between contralateral forearm skin areas ranged between 0.0 (SEsc) and 6.7 (Rmax). Conclusions The Visioscan® parameters SEr, Rmax, and Rz showed most reliable and valid values and were largely comparable on contralateral forearm skin sites in elderly subjects. Rmax, Rz, and Ra should be preferred for measuring skin surface topography with PRIMOS.